Upaya Guru Mengembangkan Kecerdasan Intrapersonal Anak Usia Dini Melalui Sentra Main Peran di TA Al-Mannar Ponorogo - Ikasari, Murni Nur (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2020)
Abatrak: The purpose of this research is to find out more deeply the steps taken by the TA Al-Manaar Al-Islamiyah Wali Songo Islamic Boarding School Ngabar Siman Ponorogo in developing intrapersonal intelligence of early childhood through role playing centers, as well as seeing the results achieved from the steps for the development of intrapersonal intelligence of early childhood, and do not forget to know the obstacles or obstacles faced by the implementation of these steps. This type of research is a qualitative research method or case study approach. Data analysis techniques are data reduction, data presentation, conclusion drawing or data verification. The results achieved by intrapersonal intelligence of early childhood in TA Al-Manaar Al-Islamiyah Ngabar have been well developed through the activities center playing roles with indicators such as self-awareness, emotional control, obeying the rules, a sense of responsibility has also been well developed. Barriers that arise, there are still children who are shy in playing a role, it takes a long time to play a role and the lack of supporting facilities in the center of role playing.